Unraveling Tax Avoidance: The Role of Financial Constraint, Thin Capitalization, and Capital Intensity in Consumer Cyclicals - Qisti, Mahya Bil; Rachmawati, Nurul Aisyah (Juara: Jurnal Riset Akuntansi, 2025)
This research aims to observe the effect of the financial constraint, thin capitalization, and capital intensity on tax avoidance practice in consumer cyclicals sub-sector companies listed on the IDX (Indonesia Stock Exchange) for the 2021-2022 period. The sample selection using the purposive sampling method from the 282 population obtained 228 samples. The analysis technique used in this study is panel data regression and hypothesis testing using STATA software. The findings of this study show that the financial constraint significantly has a negative effect on tax avoidance. While thin capitalization has no effect, capital intensity significantly positively affects tax avoidance. Based on the results testing, it proves the legitimacy theory that society has a significant effect on company value. Since the implementation of thin capitalization rules in Indonesia by the Ministry of Finance, companies in the consumer cyclicals sector prefer to use capital intensity rather than debt to carry out tax avoidance practices. Authors expect these findings to provide management, investors, and the government, as standard setters, with a consideration for decision-making.